An endless continuum : humankind´s unending journey in kinnell´s the book of nightmares = Análisis del poemario The Book of Nightmares de Galway Kinnell - Quiros García, Elizabeth
This study presents an analysis, from a mythical and archetypical stance, of the archetype of the hero's journey in Galway Kinnell's The book of nightmares. Hence, the scholarly contributions of Carl Jung, Joseph Campbell and Octavio Paz will be mainly utilized to demonstrate how the three stages of the archetype are met : separation or departure, trials and victories of initiation, and return or reintegration with society.